RANCANG BANGUN MESIN PENCETAK PENTOL UNTUK UMKM DENGAN KAPASITAS ADONAN 3KG PER JAM - Ramadhani A, Gilang; Wulandari, Diah; Puspitasari, Dewi; Nugroho, Aji (Universitas Negeri Surabaya, 2025)
This research aims to design and develop a household-scale meatball (pentol) printing machine intended for Micro, Small, and Medium Enterprises (MSMEs). The main problem faced by small-scale pentol entrepreneurs is the limitation of production tools, which are still manual, resulting in low efficiency and productivity. Therefore, the development of a pentol printing machine with a dough capacity of 3 kg per hour is expected to provide a solution in the form of a semi-automatic device that is more economical and practical for MSME use. The research method employed is Research and Development (R&D), which includes the design, manufacturing, testing, and evaluation of the pentol printing machine. The testing process used pentol dough as the material. The machine is designed with a ¼ HP electric motor at a speed of 1250 rpm and uses a screw conveyor system to push the dough. The machine frame dimensions are 400 × 300 × 450 mm, with a pulley ratio of 1:1 (2 inches / 50.8 mm) and an M-21 V-belt. A horizontal design and the addition of a cooling box are the main advantages to prevent the dough from sticking during the cutting process. The results of the design and construction tests of the pentol printing machine show that the machine operates well and is able to improve printing efficiency compared to the manual method. The machine was tested three times, each with 1 kg of dough, producing an average processing time of 3.12 minutes per kilogram. This machine is easy to operate and maintain, making it highly suitable for small business operators. With the presence of this machine, it is expected that MSMEs can increase production capacity and competitiveness in the local market. Keywords: Design and construction, Meatball printing machine, Screw conveyor.